KOMPOSISI DAN STRUKTUR VEGETASI RIPARIAN SUNGAI SUBAYANG KABUPATEN KAMPAR UNTUK PENGAYAAN MODUL KONSEP KOMUNITAS PADA MATA KULIAH EKOLOGI - Hadi N, Zamil (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study was conducted to determine the composition andstructure of the riparian vegetation along the river Subayang concept of communitydeveloped modules on the course Ecology in November 2015-January 2016. The studywas carried out by two phases: analysis of vegetation and stage enrichment module.The first phase was conducted in six sampling stations that are around the RiverSubayang, Kampar. The study used survey method Location research done by purposivesampling. Data retrieval research conducted using belt transect method that consists ofthree plots. The second stage using ADDIE development model. The results showed thatthe Riparian Vegetation Subayang River, Kampar has 21 family, 34 species and theoverall number of individuals as much as 252 people, and has a density of 348.63 ind /ha and the value of diversity index of 3.18 is high. The results of the study can be usedas a modular unit concept of community in the subject Ekololgi.Key Words: Species composition, vegetation structure, module